Difracción de Bragg de ondas ópticas guiadas por ondas de dipolo de spin en guías de onda ferromagnéticas de doble capa - Cortés-Pérez, O.; Ordoñez-Romero, C.L.; Ortega-Martínez, R.; Kolokoltsev, O.V.; Grishin, A. (Revista Mexicana de Física, 2008)
The peculiarities of the Bragg diffraction of optical guided waves (OGWs) by spin-dipole waves (SDWs) in a new ferrite heterostructure, based on Bi_3Fe_5O_12 (BIG) thin film deposited on a standard YIG/GGG (a Yttrium Iron Garnet thin film over a Galium Gadolinum Garnet substrate) sample, is presented. It is shown that the efficiency of waveguide magnetooptic interaction between OGWs and SDWs in BIG/YIG/GGG can be 4-14 times larger than in the standard YIG/GGG waveguide, even in the case when the interacting waves are localized in YIG waveguide layer.